Self-Reported Prevalence of Functional Ankle Instability and Associated Factors Among Male Football Players in Southwestern Saudi Arabia - Abdulaziz Mohammed Y Alfaya; Ahmad Alanazi; Msaad Alzhrani; Sultan A. Alanazi; Ateef Mahamed (Journal of Clinical Medicine, 2026)
Background/Objectives: Rapid changes, jumping, and high-intensity movements are common among football players and are vulnerable to ankle sprains and functional ankle instability (FAI). This study aimed to determine the prevalence of FAI and assess the correlation with related factors among male football players in southwestern Saudi Arabia. Methods: A cross-sectional observational study was conducted among 364 male football players aged ≥18 years in southwestern Saudi Arabia. Participants completed the Arabic version of the Identification of Functional Ankle Instability (Ar-IdFAI) questionnaire. Descriptive statistics were used to estimate prevalence. Differences in Ar-IdFAI scores across playing positions were examined using analysis of covariance (ANCOVA), adjusted for age, body mass index (BMI), playing experience, and weekly training hours. Multivariable binary logistic regression was used to examine factors associated with IdFAI-defined probable FAI. Results: IdFAI-defined probable FAI was identified in 47.8% (174/364) of participants (95% CI: 42.7–52.9%). After adjustment for age, BMI, playing experience, and weekly training hours, playing position was not significantly associated with Ar-IdFAI score (ANCOVA, F(3,356) = 2.106, p = 0.099). In the exploratory participant-level logistic regression analysis, greater playing experience was associated with lower odds of Ar-IdFAI-defined probable FAI (OR = 0.93, 95% CI: 0.88–0.98, p = 0.018), whereas playing position, age, BMI, weekly training hours, and dominant limb were not statistically associated with the outcome. Conclusions: FAI is prevalent among all male field-position footballers, regardless of their position. Playing position was not independently associated with instability, whereas greater playing experience demonstrated an inverse association with functional ankle instability. Findings highlight the necessity for preventive and rehabilitation approaches targeting all players regardless of position.